Authority of the Labor Inspector in Protecting Worker's Rights - ., Darwati (KnE Social Sciences, 2024)
Protection of labor rights is formulated in Law Number 13 of 2003 concerning Manpower. In order to supervise the enactment of labor rights that are formulated in the law, supervision of labor issues is needed. Formulation of the problems are based on questions such as: How is the legal protection of workers’ rights? 2. What are the legal sanctions for violations of workers’ rights? 3. What is the authority of the labor inspectorate in supervising workers’ rights? The methodologies used are normative juridical and sociological juridical. The theory used is the rule of law theory, the theory of supervision, and the theory of authority. The results of research on the legal protection of workers’ rights are regulated in Article 77, Article 78, Article 88, and Article 90 of Law Number 13 of 2003 concerning manpower. Violations of workers’ rights are subject to legal sanctions as formulated in Articles 185 and Article 187 of the Law - Law Number 13 of 2003 concerning manpower. The authority of labor inspectors is to guide and coerce violations of the law and to process criminal acts for said violations. In conclusion, labor inspectors are asked to be firm in supervising violations committed by employers. Keywords: abor inspector authority, protection of labor, protecting worker’s right